The effect of nitrogen dilution on the flammability limits of hydrogen enriched natural gas - Norlista, Saliman (2010)
Nitrogen dilution is a common procedure for ensuring safety in used of the flammable gas like hydrogen enriched natural gas which has higher burning velocity. The objective of this study is to determine the flammability limits of hydrogen enriched natural gas to the combustion and to determine the correlation of nitrogen dilution towards the hydrogen enriched natural gas. The experiment was performed in a 20L closed vessel of explosion unit. The mixtures were ignited by using spark permanent wire that place at the centre of the vessel. The pressure-time variation data during the explosion of the natural gas/hydrogen/air mixture after nitrogen is added in a vessel was recorded. Since the explosion vessel does not allow direct visual observation of the flame, the explosion vessel uses an indirect measurement of the flame propagation which is the explosion pressure. The explosion pressure data is use to determine the flammability limits of hydrogen enriched natural gas. In this study, the result shows that the flammability limits of natural gas/hydrogen/air mixture are changed after nitrogen is added into the mixture. When 7 % volume of nitrogen is added into the natural gas/ hydrogen/ air mixture, the upper flammability limit is changed from 16 % to 14 % volume of natural gas. Then, nitrogen diluted from 7 % volume up to 9 % volume of nitrogen reduces the upper flammability limit of hydrogen enriched natural gas from 14 % to 11 % of natural gas by volume. So, the range of the flammability limits also reduced when the volume of nitrogen is increased.